Calibration of Holmquist Johnson Cook (HJC) model for projectile penetration of geopolymer-based ultra-high performance concrete (G-UHPC). (September 2022) - Liu, Jian; Liu, Cheng; Qu, Kefo; Li, Jun; Wu, Chengqing
Abstract: Holmquist Johnson Cook (HJC) model has been extensively adopted to simulate the projectile penetration of concrete targets. In this study, based on the available experimental data of uniaxial compression, triaxial compression, split Hopkinson pressure bar (SHPB) and Hugoniot tests, HJC model parameters in terms of the strength surface, strain rate effect, damage evolution and equation of state (EOS) were systematically calibrated for a newly fabricated ultra-high performance concrete termed as geopolymer-based ultra-high performance concrete (G-UHPC). Using the HJC model with calibrated model parameters, numerical simulations of projectile penetration into plain and fibre reinforced G-UHPC targets were performed in a commercial finite element program LS-DYNA. The numerical results for the depth of penetration (DOP) exhibited fair agreement with the test data. The numerical projectile velocity and displacement evolutions were also validated through comparing to the semi-analytical model. These observations demonstrated the applicability and validity of the calibrated HJC model to estimate DOP of G-UHPC targets subjected to projectile impact. With the calibrated and validated HJC model, parametric studies were further conducted to explore the effect of uniaxial compressive strength of G-UHPC, projectile impact velocity, mass, diameter and nose shape on the final DOP values. Based on the numerical results from the parametric studies, an empirical equation concerning the aforementioned variables was proposed, which could help design G-UHPC protective barriers against projectile penetration.